1986
DOI: 10.1111/j.1463-6395.1986.tb00868.x
|View full text |Cite
|
Sign up to set email alerts
|

A Rostral Sensory Mechanism in Oikopleura dioica (Appendicularia)

Abstract: Bollner, T., Holmberg, K., Olsson, R. 1986. A rostra1 sensory mechanism in Oikopleura dioica (Appendicularia). (Department of Zoology, University of Stockholm, Sweden.)-Acta zoof. (Stockh.) 67, 235-241.The ventral sense organ, below the mouth, is composed of 30 primary sensory cells situated in a row perpendicular to the long axis of the animal. Each cell carries one long and slender, modified cilium which arises from ap apical pocket in the cell. The sensory cells project 15 axons at each side of the pharynx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…It therefore appears that Amphi-GPCR-positive cells may be preliminary versions of the vertebrate olfactory sensory neurons, and that they could be supposed to be chemosensory in function. Bollner et al (1986) observed primary sensory neurons in the rostral epithelium of appendicularians, which represent a sister-group of the clade of the other urochordates (Wada, 1998), and proposed that they were counterparts of the vertebrate olfactory sensory neurons. If so, olfactory-related chemosensory cells in the rostrum may be a shared feature of the chordates.…”
Section: Evolutionary History Of Olfactory Sensory Neurons and Its Simentioning
confidence: 99%
“…It therefore appears that Amphi-GPCR-positive cells may be preliminary versions of the vertebrate olfactory sensory neurons, and that they could be supposed to be chemosensory in function. Bollner et al (1986) observed primary sensory neurons in the rostral epithelium of appendicularians, which represent a sister-group of the clade of the other urochordates (Wada, 1998), and proposed that they were counterparts of the vertebrate olfactory sensory neurons. If so, olfactory-related chemosensory cells in the rostrum may be a shared feature of the chordates.…”
Section: Evolutionary History Of Olfactory Sensory Neurons and Its Simentioning
confidence: 99%
“…Olsson, 1986;Cañestro et al, 2005). Its CNS consists of an enlargement, the 'anterior brain', containing fewer than 70 cells (Georges et al, 1988;Martini, 1909) (Fig.…”
Section: Investigating Morphology Of Candidate Placodes In Oikopleuramentioning
confidence: 99%
“…These cells are primary sensory cells like vertebrate olfactory receptor cells, and their axons integrate into the rostral-most CNS (Bollner et al, 1986). To reflect these structural similarities to the vertebrate olfactory epithelium, they were called olfactory or chemosensory cells by various authors, although their function is unknown (Bollner et al, 1986;Lohmann, 1933).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations